Buyer- seller relationship and the performance of micro retail businesses in Tanzania - Fredson, Prince (Mzumbe University, 2024)
A Dissertation Submitted in Partial Fulfillment of the Requirement for the Award of the Degree of Master of Science in Procurement and Supply Chain Management of Mzumbe University 2018